Social life cycle assessment of the olive oil industry: a case study in Guilan Province, Iran - Behzad Safeie-Noghlbari (21767705) (2024)
Olive oil production has severe environmental consequences, including resource depletion, land degradation, carbon emissions, and waste generation. As a result, for over two decades, environmental life cycle assessment (ELCA) has been applied to the olive oil industry to identify environmental issues and reduce the environmental effects. However, little is known regarding the social sustainability of this industry. Social life cycle assessment (S-LCA) has been established as one of the most effective methodologies for assessing the social implications of products throughout their life cycles. Accordingly, based on the S-LCA approach, this study aims to assess the social impacts of the olive oil extraction industry in Roudbar County in Guilan Province in Iran, the major producer of olives and olive oil. The S-LCA model adopted in this paper is built in four major phases (UNEP/SETAC in Guidelines for social life cycle assessment of products, 2009): (1) Definition of Goal and Scope: outlines the intended use and the goal pursued and specifies the scope of the research. The research will then be defined to fulfill that purpose within any constraints. (2) Life Cycle Inventory analysis: is the phase at which data are collected, systems are modeled, and LCI results are generated. (3) Life Cycle Impact Assessment: a collection of steps to obtain data categorization, aggregation, and characterization based on performance reference points. (4) Life Cycle Interpretation: considers all important aspects of the research when drawing results, offering recommendations, and reporting. The findings suggested that the social conditions governing the olive oil extraction cycle in the study area are almost adequate. However, other categories of social impacts, such as cultural heritage, community development, and working conditions, were rated unsatisfactory by olive orchard workers and need improvement. Adopting the cause-and-effect chain in this study favors identifying specific indicators based on social issues in the study location. On the other hand, a scale-based assessment may result in the subjectivity of the results, which adds to the uncertainty. An impact-based assessment may be applied to analyze social impacts such as occupational health and safety, employment, pay, and benefits to get more credible social impact data. Consequently, integrating the scale-based approach with an efficient path-based method may improve its effectiveness. Other Information Published in: Environment, Development and Sustainability License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10668-024-04463-2